Blood transfusions in critically ill cancer patients remain an area of uncertainty - Malik, Imrana Alam; Reinhart, Konrad (Journal of Emergency and Critical Care Medicine, 2017)
In a single center, randomized, controlled trial entitled “Liberal Versus Restrictive Transfusion Strategy in Critically Ill Oncologic Patients: The Transfusion Requirements in Critically Ill Oncologic Patients Randomized Controlled Trial”, the authors conclude that a liberal strategy for blood transfusions (hemoglobin threshold